Dysregulated glycerophospholipid metabolism in amygdala may mediate favipiravir-induced anxiety-like behaviors in mice - Xiao, Yuzhou; Liu, Chunqi; Wang, Xiaojie; Li, Hongchun; Wang, Liang; Gou, Kun; Liu, Xingchen; Guan, Xinqi; Zhou, Xia; He, Xiumei; Zhao, Yue; Tao, Lei; et al. (Frontiers in Pharmacology, 2025)
Favipiravir, the first RNA polymerase inhibitor approved to treat resistant influenza, has been reported to be associated with central nervous system (CNS) side effects, particularly anxiety-like behavior; nevertheless, the underlying mechanism remains largely unknown. In this study, we investigated the effect of favipiravir on the neurobehavior of mice, and combined lipidomics and transcriptomics analysis to explore the mechanism underlying this effect. In behavioral tests, the mice displayed anxiety-like behaviors after oral favipiravir administration (200 mg/kg) for 7 days continuously. By lipidomics analysis, we observed that favipiravir induced a dysregulation of glycerophospholipid metabolism in the amygdala. Moreover, favipiravir significantly reduced the mRNA level of glycerol-3-phosphate acyltransferase 2 (Gpat2), the rate-limiting enzyme of glycerophospholipid synthesis. Notably, favipiravir markedly reduced the levels of docosahexaenoic acid-enriched phosphatidylethanolamine or phosphatidylcholine (DHA-PE/PC) and arachidonic acid-enriched phosphatidylethanolamine or phosphatidylcholine (AA-PE/PC), two components of glycerophospholipids, in the amygdala. The increased expression of phospholipase A2 (Pla2) may attribute to the enhanced release of arachidonic acid (AA) from AA-PE/PC. Furthermore, favipiravir altered neurite morphology and reduced neurophysiological activity in amygdala neurons in vitro. Collectively, dysregulated glycerophospholipid metabolism in the amygdala may contribute to the adverse effect of favipiravir.